ENVIRONMENT BASED EDUCATION AS A PROCESS FORMATION OF CHILD CHARACTER - Tihazanah; Siti Mayang Sari; Akmaluddin; Lili Kasmin (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
This study uses a descriptive qualitative method by looking at the phenomenon of problems in education today. Children's education as an initial level is the formation of character in each individual. Good guidance is needed in real life as a character builder in children. Learning in children will greatly affect the personality of individuals as adults. This study aims to find out how the form of character that should be instilled in children so they don't fall into an environment that is prone to violence. This research will produce school rules and regulations as a friendly school and make children later have good character and personality. Based on the formation of children's character, the provision of educators will be able to realize child-friendly schools according to existing standards, must comply with the protection of violence against children and give students the freedom to express themselves under school supervision. Fulfillment of facilities and infrastructure to support the teaching and learning process is fulfilled. Basically, facilities and infrastructure really help children in their environment, both social and individual in developing their interests and talents, which must be fulfilled, such as properties that will be used in the teaching and learning process. It can be concluded that a child will have a personality or character influenced by the education he receives. The formation of children's character comes from education and teacher guidance to protect children in the event of violence that occurs.